Glycine 100 in the dinitrogenase reductase of Rhodospirillum rubrum is required for nitrogen fixation but not for ADP-ribosylation. - Lehman, L J (1991)
Dinitrogenase reductase (Rr2) is required for reduction of the molybdenum dinitrogenase in the nitrogen fixation reaction and is the target of posttranslational regulation in Rhodospirillum rubrum. This posttranslational regulation involves the ADP-ribosylation of Rr2. To study the structural requirements for these two functions of Rr2, i.e., activity and regulation, two site-directed mutations in nifH, the gene encoding Rr2, were constructed and analyzed. The mutations both affected a region of the protein known to be highly conserved in evolution and to be relevant to both of the above properties. These mutants were both Nif-, but one of the altered Rr2s was a substrate for ADP-ribosylation. This demonstrates that the ability of Rr2 to participate in nitrogen fixation can be separated from its ability to act as a substrate for ADP-ribosylation.